On the relation between technical debt indicators and quality criteria in Stack Overflow discussions - Costa, Diego; Cortés, Mariela; Gama, Eliakim (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Context: Technical debt (TD) can compromise the quality of software systems in the long term. However, depending on the needs and properties of the specific product, different quality characteristics may be considered in the assessment with different levels of relevance. In this way, quality characteristics can guide teams in managing the TD, from identifying to paying for the TD items relevant to each situation. Although a set of TD item indicators has been identified in the literature, there is no clear guidance on how these indicators can be efficiently used to identify TD items. Aims: To investigate, from the point of view of software professionals using the SO platform, the relationship between the TD item indicators and the quality characteristics of the system, in order to guide the use of indicators for greater efficiency and effectiveness in identifying and managing DT items from a quality perspective. Method: We extracted empirical evidence using data mining from discussions related to TD on the SO. From the execution of an analysis process, the quality characteristics related to the occurrence of DT items identified in the discussions, the respective indicators and types of debt were identified. Results: The main results reveal that maintainability is the characteristic most related to TD through its sub-characteristics: modifiability, testability and modularity. Code debt items can be related to all quality characteristics, while Infrastructure debt can resonate up to 6 characteristics. All quality characteristics have at least one associated indicator, with an emphasis on Maintainability with 13 high-level and 28 low-level indicators. The indicator related to version problems is the one with the highest number of quality features. Conclusion: The relationship between indicators, TD types and quality characteristics was organized in a conceptual diagram in order to assist software teams in identifying which TD items are related to the quality characteristics that are critical to the project context, contributing to decision making regarding the best strategy for debt management.